Pengaruh Terapi Atorvastatin terhadap Kadar Glukosa Darah pada Pasien Stroke Iskemik dengan Diabetes Melitus yang Dirawat di Rumah Sakit - Dwi Evi Diyan Sari; Erni Anika Sari; Faizatul Fitria; Hariyani Hariyani; Krisogonus Ephriono Seran; Shofiatul Fajriyah; Yogi Bhakti Marhenta; Alissya Okta Nanda Agustina (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: The use of atorvastatin in patients with stroke as a primary preventive therapy may be associated with an increased risk of elevated blood glucose levels. This study aimed to evaluate the effect of atorvastatin on changes in blood glucose levels in patients with ischemic stroke. Methods: An analytical observational study with a retrospective design was conducted among 28 hospitalized patients with ischemic stroke at Bhayangkara Hospital, Kediri City, from March to April 2024. Inclusion criteria comprised patients aged >15 years, with a history of diabetes mellitus, receiving atorvastatin therapy, and having available blood glucose data before and three days after treatment initiation. Data were analyzed using the Shapiro–Wilk test to assess normality and the paired sample t-test to evaluate changes in blood glucose levels. Results: A total of 64,29% of patients experienced an increase in blood glucose levels; however, statistical analysis demonstrated no significant difference between blood glucose levels before and after atorvastatin administration (231.64 ± 99.039 vs 231.50 ± 61.425 mg/dL; Δ = −0.14 mg/dL; p= 0.993). Conclusion: Atorvastatin therapy was not associated with statistically significant changes in random blood glucose levels. However, the high proportion of patients with increased blood glucose warrants further prospective investigation.